PENERAPAN TEKNOLOGI BIG DATA DENGAN EVALUASI KEMATANGAN COMPLIANCE RISK MANAGEMENT (CRM) TERHADAP TAX COMPLIANCE DI ERA DIGITAL - Astuti, Puji; Rapina, Rapina (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
The government seeks to optimize state revenue, one of which is by increasing taxpayer compliance (Riris, 2020). The level of formal compliance over the past 5 years has fluctuated, the ratio of SPT submission in 2017 was 72.58%, in 2018 it fell to 71.1% and in 2023 out of a total of 19.4 million taxpayers only 17.1 million taxpayers have carried out their obligations at the end of 2023 (Hariani, 2023). This research discusses the Application of Big Data Technology with CRM Maturity Evaluation to Tax Compliance in the Digital Era. This study aims to monitor how Big Data and CRM technology can assist DGT in improving formal and material compliance. By utilizing data from various sources including social media, DGT can improve efficiency in the taxation process. The implication of this research is the importance of the integration of Big data and CRM technology in increasing state revenue through increasing taxpayer compliance. The research method used is quantitative with a descriptive approach and verification analysis, hypothesis testing is done with primary data in the form of questionnaires distributed to Account Representatives (AR) in the West Java I Regional Office. The sampling technique used purposive sampling. The results of this study indicate that the application of big data (X1), and CRM (X2) has a significant taxpayer compliance in the digital era (Y).